A Thresholdless Tunable Raman Nanolaser using a ZnO–Graphene Superlattice. Issue 2 (9th November 2016) - Zhu, Haiou; Xu, Xintong; Tian, Xiaoqing; Tang, Jiaoning; Liang, Huawei; Chen, Lingling; Xie, Yi; Zhang, Xiaodong; Xiao, Chong; Li, Ran; Gu, Qiao; Hua, Ping; et al.
Abstract : A ZnO–graphene superlattice is synthesised via a spatially confined reaction. When illuminated by a pump laser, the Stokes' photons of the superlattice are greatly amplified by the surface plasmon at the interface of the graphene and the ZnO. Benefitting from the special geometry, the ZnO–graphene superlattice allows the generation of a tunable nanolaser that operates from the visible to near‐infrared range at room temperature.